Strategies for Managing Human Resources: Enhancing PAI Teachers’ Digital Literacy in Bawang: Strategi Pengelolaan Sumber Daya Manusia: Meningkatkan Literasi Digital Guru PAI di Bawang Banjarnegara - Dwi Kuswianto; Umi Labibah (Fakultas Tarbiyah Dan Ilmu Keguruan Institut Agama Islam An-Nawawi Purworejo, 2024)
This study explores the dynamics of Human Resource (HR) management in addressing the digital literacy gap among Islamic Religious Education (PAI) teachers within the rural context of Bawang District, Banjarnegara. Utilizing a qualitative descriptive design, the investigation involves a comprehensive analysis of data obtained through field observations and semi-structured interviews conducted in August 2025 with the PAI Teachers Working Group (KKG). The findings reveal a significant paradox where the extensive provision of modern infrastructure, such as Chromebooks and Android TVs, fails to yield optimal technological integration due to deep-seated andragogical barriers among senior educators. To mitigate this challenge, the KKG employs a strategic peer-teaching framework, institutionalizing a collaborative environment where younger, tech-savvy teachers facilitate the digital administrative workflows of their senior counterparts, particularly in managing the SIAGA platform. Ultimately, this research underscores that sustainable digital transformation in religious education necessitates a personalized, human-centered management approach that transcends mere hardware distribution, prioritizing psychological readiness and intergenerational symbiosis.